zapisz w jak najprosyszej postaci: a) 3(a-2)=. b) -3b2(b2-1)=. c)3x-6xy+1-3=. d)2x (x-5)-3(x2-2x)+(x-2)x=. e)a(a+b+c)-b(a-b+c)-c(a-b-c)=​



Odpowiedź :

Odpowiedź:

a)

3(a-2)= 3a - 6

b)

-3b²(b²-1)= -3b^4 + 3b²

c)

3x-6xy+1-3= 3x - 6xy - 2

d)

2x (x-5)-3(x2-2x)+(x-2)x= 2x² - 10x - 3x² + 6x + x² - 2x = -6x

e)

a(a + b + c) - b(a - b + c) - c(a - b - c) = a² + ab + ac - ab + b² - bc - ac + bc + c² = a² + b² + c²​

Szczegółowe wyjaśnienie:

[tex]3(a-2)=3a-6\\\\-3b^2(b^2-1)=-3b^4+3b^2\\\\3x-6xy+1-3=3x-6xy-2\\\\2x (x-5)-3(x^2-2x)+(x-2)x=\\2x^2-10x-x^2+6x+x-2=x^2-3x-2\\\\a(a+b+c)-b(a-b+c)-c(a-b-c)=\\a^2+ab+ac-ab+b^2-bc-ac+bc+c^2=a^2+b^2+c^2[/tex]